Achieving a Covid-19 Free Country: Citizens Preventive Measures and Communication Pathways - Kamenidou, Irene (Eirini) (Int J Environ Res Public Health, 2020)
The Coronavirus Disease 2019 (COVID-19) has spread on a global scale in an extremely short time, causing hundreds of thousands of deaths, and, at the same time, triggering extreme panic. Prevention in medicine is considered the best protection action for individuals in order to avoid infections. This study investigates whether Greek citizens (N = 3359) take the necessary precautions to prevent developing the COVID-19 disease, and it segments them based on homogenous behavior groups. Lastly, it provides communication techniques that should be implemented, targeting each citizen segment for a long-term COVID-19 free country. Data analysis revealed the extent of the applied precaution measures. The ones most applied by citizens were to avoid non-mandatory transportation, contact with individuals with respiratory symptoms, and individuals of high risk for severe illness (vulnerable groups). On the other hand, the least applied measures are daily checks of body temperature, monitoring for fever, cough, or dyspnea, use of a face mask when in public places, or when using public transportation. Additionally, cluster analysis revealed five groups of citizens based on self-reported behavior, namely, the Meticulous Proactive Citizens, the Self-isolated Citizens, the Cautious Citizens, the Occasionally Cautious Citizens, and the Unconcerned Citizens. Communication strategies targeting each segment are also discussed.